The Effect of Leadership Style on Employee Performance of the PPIC Division of PT. Prima Components Indonesia BSD-Tangerang - Suyatin Suyatin (PINISI Discretion Review, 2019)
The automotive industry is one of the mainstay sectors whose development continues to be prioritized. The purpose of this study was to determine the effect of leadership style on the performance of the employees of PT. Prima Components Indonesia BSD-Tangerang. The research method uses quantitative, saturated sampling, which means that the entire population is sampled as many as 45 respondents. Statistical tests use simple linear regression equations, correlation coefficient tests, determination coefficient tests, and significance tests. The results of the study found that there was an influence of leadership style on the performance of employees of the PPIC Division of the Department of PT. Prima Components Indonesia BSD-Tangerang, based on the results of data analysis shows that from the correlation of 0.619 it can be concluded that there is a strong influence between leadership style on the employee performance of the PPIC Division of the Department of PT. Prima Components Indonesia BSD-Tangerang, The results of the coefficient of the determination indicate that the leadership style contributes 38.3% to employee performance, the remaining 61.7% is influenced by other variables. Simple linear regression equation Y = 1.454 + 0.629X In the hypothesis test tcount 5.163> ttable 1.68 then Ho is rejected H1 is accepted, meaning that there is a significant influence between leadership style on employee performance at the PPIC Department of PT. Prima Components Indonesia BSD-Tangerang.